O potrzebie zarządzania ryzykiem operacyjnym w instytucjach finansowych - Matkowski, Paweł (The Neccesity of Operational Risk Management in Financial Institutions, 2005)
The approach of Enterprise-wide Risk Management in financial institutions requires dealing with operational risk, besides credit and market risk. The growing operational risk exposure is a result of an increased importance of internationally active banks and appearance of rare events. The surveys j show that operational risk is responsible for approximately 35% earning volatility of banks. That was the main reason that regulators decided to include operational risk in New Adequacy Framework. This working paper presents a review of the literature of operational risk management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 198-215